Elevated tissue inhibitor of metalloproteinase-1 along with left atrium hypertrophy predict atrial fibrillation recurrence after catheter ablation - Sun, Weiping; Li, Haiwei; Wang, Zefeng; Li, Qin; Wen, Haichu; Wu, Yongquan; Du, Jie (Frontiers in Cardiovascular Medicine, 2022)
This study aimed to establish a model that predicts atrial fibrillation (AF) recurrence after catheter ablation using clinical risk factors and biomarkers. We use a prospective cohort study, including 230 consecutive AF patients successfully treated with catheter ablation from January 2019 to December 2020 in our hospital. AF recurrence was followed-up after catheter ablation, and clinical risk factors and biomarkers for AF recurrence were analyzed. AF recurred after radiofrequency ablation in 72 (31%) patients. Multiple multivariate logistic regression analysis demonstrated that tissue inhibitor of metalloproteinase-1(TIMP1) and left atrium diameter (LAd) were closely associated with AF recurrence. The prediction model constructed by combining TIMP1 and LAd effectively predicted AF recurrence. Additionally, the model’s performance discrimination, accuracy, and calibration were confirmed through internal validation using bootstrap resampling (1000 times). The model showed good fitting (Hosmer–Lemeshow goodness, HL chi-square 3.76138, p=0.926) and had a superior discrimination ability (the area under the receiver operation characteristic curve, AUC, 0.917 ;95%CI 0.882–0.952). The calibration curve shows good agreement between the predicted probability and the actual probability. Moreover, the decision curve analysis (DCA) showed the clinical useful of the nomogram. In conclusion, predictive model based on serum TIMP-1 and LAd levels can predict AF recurrence after catheter ablation.